Turtles - Marsh, Laura F.; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2016)
"Take a dip with turtles in this exciting reader. Packed with beautiful and engaging photos, kids will learn all about these fantastic reptiles. This Level 1 reader is carefully leveled for an early independent reading or read aloud experience, perfect to encourage the scientists and explorers of tomorrow!"--Provided by publisher.
Tons of turtles -- Turtles and tortoises -- Parts for safety -- Cool facts about turtles -- Crunch and munch -- Tiny turtles -- Life in the sea -- Terrific turtles! -- A helping hand -- What in the world?
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 4-6.
Print version record.
Keywords: Turtles -- Juvenile literature; Sea turtles -- Juvenile literature; Sea turtles; Turtles; Electronic books- OSLIS; Juvenile works; Electronic books